Cuantificación de flavonoides totales en los extractos hidroalcohólicos de las hojas de piper aduncum “matico” procedentes del distrito de Chota, departamento de Cajamarca y del jardín botánico “Rosa Elena de los Ríos Martínez” de la Universidad Nacional de Trujillo - Valle Vargas, Brenda Jakeline (2014)
The purpose of the present investigation was the quantification of total flavonoids expressed as quercetin in the hydroalcoholic extracts of the leaves of Piper aduncum “matico”. The Samples were collected in the district of Chota, department of Cajamarca and in the Botanical Garden "Rosa Elena Rios Martinez " at the National University of Trujillo" in February-2012. The preliminary identification of flavonoids was performed through by reaction of Shinoda and the reaction with concentrated sulfuric acid; in the reaction of Shinoda was obtained a red coloration and in the reaction with concentrated sulfuric acid was obtained an intense yellow coloration; both colorations indicate the presence flavones and flavonols in the prepared hydroalcoholic extracts. Subsequently the quantification of flavonoids was performed using the spectrophotometric technique, it was found that the amount of total flavonoids expressed as quercetin in hydroalcoholic extract of the leaves of Piper aduncum “matico” from the district of Chota, Cajamarca was 0,0201 mg / mL in compared with 0,0097 mg/ mL, amount of total flavonoids expressed as quercetin found in the hydroalcoholic extract of the leaves of Piper aduncum “matico” of the Botanical garden "Rosa Elena Rios Martinez" at the UNT